Chronic total occlusions—Is true lumen wire passage preferred to subintimal dissection re‐entry?. Issue 6 (25th April 2019) - Feldman, Marc D.; Michalek, Joel
Key Points: True lumen crossing is superior to subintimal crossing. Subintimal versus true lumen crossing may only be apparent if IVUS is performed. Newer techniques for true lumen crossing need to be developed.